2023
DOI: 10.1590/1519-6984.247913
|View full text |Cite
|
Sign up to set email alerts
|

Lumbriculus variegatus (Müller, 1774) (Oligochaeta, Lumbriculidae) in Campos do Jordão State Park, São Paulo, Brazil

Abstract: The aim of this paper was recording the occurrence of the species Lumbriculus variegatus (Müller, 1774) (Oligochaeta, Lumbriculidae) in lotic systems of the State of São Paulo. Specimens were collected in Sapucaí River, located in Campos do Jordão State Park. The mapping of geographical distribution of this species is of interest to public health since L. variegatus may be an intermediate host of Dioctophyme renale (Goeze, 1782) (Nematoda, Dioctophymatidae), a parasite of recognized zoonotic potential. Distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The chosen LULC classes for the project were: The methodology used for the classification is summarized in Figure 2. ___________________________________________________________________________ on water bodies inside the UC is abundant, as shown by studies conducted in its premises (Gorni & Alves, 2008;Segura et al, 2012;Sanches et al, 2021) As shown by Modenesi-Gauttieri and Hiruma ( 2004), the urban expansion of Campos do Jordão is greatly increasing over the years, resulting on many instabilities on the soil thanks to the incorrect land use, another problem with the intensification of LULC changes is the need of deforestation on the area, which also contributes to the endangerment of species and specially citizens who can be subjected to floods and landslides.…”
Section: Image Classificationmentioning
confidence: 99%
“…The chosen LULC classes for the project were: The methodology used for the classification is summarized in Figure 2. ___________________________________________________________________________ on water bodies inside the UC is abundant, as shown by studies conducted in its premises (Gorni & Alves, 2008;Segura et al, 2012;Sanches et al, 2021) As shown by Modenesi-Gauttieri and Hiruma ( 2004), the urban expansion of Campos do Jordão is greatly increasing over the years, resulting on many instabilities on the soil thanks to the incorrect land use, another problem with the intensification of LULC changes is the need of deforestation on the area, which also contributes to the endangerment of species and specially citizens who can be subjected to floods and landslides.…”
Section: Image Classificationmentioning
confidence: 99%